Islamic Soft Skills Development for Madrasah-Age Children through an Integrated Didikan Subuh Program at MIN 3 South Labuhanbatu - Rizki Hafni Rambe; Zulhimma (International Journal Of Economics Social And Technology, 2025)
Developing Islamic soft skills in madrasah-aged children is crucial for developing a religious character aligned with the values ​​of everyday life. The integrated Dawn Reading program at MIN 3 Labuhanbatu Selatan is a systematic effort to instill Islamic values ​​in students. A qualitative descriptive approach with strategic field studies is used to describe the implementation of activities in depth through observation, direct interaction, and documentation. A series of events, including recitation of Islamic verses (Quran), recitation of Quranic verses (Surah), memorization (tahfiz), nasyid (Islamic nasheed), prayers, and prayer practices, serve as a means for students to strengthen their religious understanding while simultaneously practicing social and spiritual skills. The implementation of Dawn Reading has had a positive impact on the development of students' Islamic soft skills, including discipline, responsibility, cooperation, respect, and worship skills. The religious madrasah environment and the role of teachers as mentors and role models also strengthen the internalization of these values. Activities carried out outside the classroom create a more open and enjoyable learning atmosphere, so that children feel comfortable and are motivated to participate actively. Overall, Dawn Education significantly contributes to the formation of Islamic character, which is reflected in students' daily behavior. It can be concluded that Dawn Education is integrated into an effective character training method because it is implemented routinely, structured, and directly involves students in various religious activities. To strengthen its impact, it is necessary to develop a variety of learning methods, improve teacher and student competencies, and involve parents in continuing the instillation of Islamic values ​​in the home environment, so that character formation can take place comprehensively and sustainably.